2017
DOI: 10.22159/ijpps.2017v9i5.17289
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological Evaluation of Medicinal Plants for Cytotoxicity Against Various Cancer Cell Lines

Abstract: Objective: To evaluate the cytotoxic potential of leaves and seeds of Hibiscus sabdariffa L., fruit juice of Phyllanthus emblica, rhizomes of Dryopteris cochleata and flowers of Caesalpinia decapetala (Roth) Alston along with the chemical profiling of the most toxic extract through Gas-mass spectroscopy-MS technique. Methods:The hydroalcoholic extract of the selected crude drugs was prepared by maceration method and the extracts were undergone through phytochemical analysis. The cytotoxic activity of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…have been reported for its antioxidant, antipyretic, antimicrobial, anticancer, anti-inflammatory, immunomodulatory, hypolipidemic, and hepatoprotective properties [20][21][22][23][24][25][26][27]. The methanolic extract of P. emblica has been reported for the bacterial efflux pump inhibiting activity [28].…”
Section: Resultsmentioning
confidence: 99%
“…have been reported for its antioxidant, antipyretic, antimicrobial, anticancer, anti-inflammatory, immunomodulatory, hypolipidemic, and hepatoprotective properties [20][21][22][23][24][25][26][27]. The methanolic extract of P. emblica has been reported for the bacterial efflux pump inhibiting activity [28].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been revealed that some antioxidants (e.g., quercetin and naringenin) are able to inhibit cytochrome P450 enzymes (CYP1A1 and CYP3A4, respectively) involved in the bioactivation of chemical carcinogens [28], constituting another proposed chemopreventive mechanism of polyphenols against cancer development including lung cancer [104,105].…”
Section: Antioxidants Against Cancermentioning
confidence: 99%
“…Anthropogenic activities, urbanization, accelerated industrialization, extensive growth of exotic aquatic weeds, encroachments, frequent, and excessive collection of aquatic resources are the major causes of the degradation of majority of the wetlands of Assam. Many works have studied on medicinal uses of the plants of Northeast India and abroad [11,12]. So far, no detail ethnomedicinal study of aquatic macrophytes of the wetlands of Kamrup district of Assam, India, has been reported by any worker.…”
Section: Introductionmentioning
confidence: 99%